ANALISIS STABILITAS MULTI MACHINE PADA ISLAND MODE SISTEM KELISTRIKAN BALI - I Gede Bayu Suarsa; Ida Bagus Gede Manuaba; Rukmi Sari Hartati (Jurnal SPEKTRUM, 2020)
Modern electrical systems are characterized by extensive interconnection systemswith the need for electrical energy and control depending on the control system. Oneelectricity system that has been widely interconnected is the Bali electricity system. The Balisystem using island mode has four generating units that can supply electrical energy needsincluding UP Pesanggaran, UP Celukan Bawang, UP Gilimanuk and UP Pemaron. But itmust be remembered in supplying electrical energy needs are also affected by the constantchange in load, resulting in instability in the electrical system. So the need for a controlsystem that can increase the value of damper such as the Power System Stabilizer (PSS). PSScan be used to reduce frequency oscillations when interference occurs, but for PSS design itgives less good performance in different operating conditions. Problems with PSS occur dueto errors in modeling, input value input, and topology variations. Efforts are made to reduceerrors in PSS by using methods that are expected to overcome this problem, namely the fuzzylogic controller.The results of the analysis show that the system performance index usingfuzzy logic is 78.6064. Fuzzy logic has the ability to damp better and reduce errors better.